A Single Thermoresponsive Diblock Copolymer Can Form Spheres, Worms or Vesicles in Aqueous Solution. (6th November 2019) - Ratcliffe, Liam P. D.; Derry, Matthew J.; Ianiro, Alessandro; Tuinier, Remco; Armes, Steven P.
Abstract: It is well‐known that the self‐assembly of AB diblock copolymers in solution can produce various morphologies depending on the relative volume fraction of each block. Recently, polymerization‐induced self‐assembly (PISA) has become widely recognized as a powerful platform technology for the rational design and efficient synthesis of a wide range of block copolymer nano‐objects. In this study, PISA is used to prepare a new thermoresponsive poly( N ‐(2‐hydroxypropyl) methacrylamide)‐poly(2‐hydroxypropyl methacrylate) [PHPMAC‐PHPMA] diblock copolymer. Remarkably, TEM, rheology and SAXS studies indicate that a single copolymer composition can form well‐defined spheres (4 °C), worms (22 °C) or vesicles (50 °C) in aqueous solution. Given that the two monomer repeat units have almost identical chemical structures, this system is particularly well‐suited to theoretical analysis. Self‐consistent mean field theory suggests this rich self‐assembly behavior is the result of the greater degree of hydration of the PHPMA block at lower temperature, which is in agreement with variable temperature 1 H NMR studies. Abstract : Formenvielfalt : Ein amphiphiles, thermoresponsives Diblockcopolymer kann reversibel Kugeln, Würmer oder Vesikel in wässriger Lösung bilden. Theoretische Studien zeigen, dass dieses reichhaltige Selbstorganisationsverhalten aus dem temperaturabhängigen Hydratationsgrad des strukturdirigierenden hydrophoben Poly(2‐hydroxypropylmethacrylat)‐Blocks resultiert.